Faktor Predisposisi Pengetahuan, Sikap, Nilai dan Budaya Eks Wanita Pekerja Seksual dengan Kejadian HIV/AIDS di Wilayah Kediri - Jayani, Indah; Ruffaida, Fatma Sayekti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Human Immunodeficiency Virus (HIV)/ Immuno Deficiency Syndrome (AIDS) is a global health problem as a cause of a high mortality rate. The phenomenon of an increase in HIV/AIDS infection in the Kediri region was mostly obtained from the former Sexual Workers Woman (WPS). The purpose of the study was to determine the correlation between knowledge, attitudes, values and culture with the prevalence of HIV/AIDS among former sexual worker women in Kediri, East Java Province. This study was a correlation analytic study with a cross sectional. The population in this study was 448 with a proportional stratifed sampling technique which obtained a sample of 58 people. The instrument used in data collection is questionnaire. The results of the analysis with the Spearman rank correlation test showed there was a strong negative correlation between knowledge with HIV/AIDS events (ρ=0,00; r=-0,571), a strong negative correlation between attitudes and HIV/AIDS events (ρ=0,00; r=-0,538), a strong negative correlation between value and HIV/AIDS events (ρ=0,00; r=-0,784) and a strong negative correlation between cultures and HIV/AIDS events was indicated by (ρ=0,00; r=-0,456) among former WPS in Kediri, East Java Province 2017. Based on the results, the suggestions for health workers and related social services should continue to improve services by providing continuous education to former WPS related to how HIV/AIDS prevention and transmission are carried out, providing assistance, monitoring bio, psycho, socio-spiritual to change attitudes maladaptive becomes adaptive, and to disseminate culture to reduce the risk of HIV/ AIDS.